An ancient coronavirus from individuals in France, circa 16th century. (June 2023) - Oumarou Hama, Hamadou; Chenal, Thomas; Pible, Olivier; Miotello, Guylaine; Armengaud, Jean; Drancourt, Michel
Highlights: The antiquity of human-associated coronavirus (HCoV) is poorly known. Dental pulp paleoproteomics investigated HCoV in two individuals from the 16th century. HCoV peptides and antibodies were found. These findings confirmed HCoV in past populations. Abstract: Objectives: At the time when the COVID-19 pandemic was responsible for more than six million deaths worldwide, the antiquity of coronaviruses remains undefined. We investigated individuals buried during the 16th century in France for the direct and paleoserological diagnosis of the coronavirus. Methods: The 2011-2012 excavation of Abbey Saint-Pierre in Baume-Les-Messieurs, France uncovered 12 skeletons of individuals from the 13th to the 18th century. The total proteins extracted from dental pulps were subjected to microbial paleoserology, targeting SARS-CoV-2, human-associated coronavirus (HCoV)-229E, and OC43 antigens and for coronavirus peptide research using metaproteomics, in parallel to negative controls. Results: Three peptide sequences totaling 36 amino acids indicative of a coronavirus were retrieved from the dental pulp remains collected from two individuals buried circa 16th century, in whom paleoserology confirmed a specific immunological response against modern-day SARS-CoV-2 and HCoV-229E. Conclusion: We provide serological and proteomic evidence for a betacoronavirus with no modern correspondent, infecting populations in the 16th century, extending the antiquity of coronaviruses by more than three centuries. Historical, archaeozoological, and paleoproteomic data suggested close contacts between these two individuals and domestic swine, cattle, and poultry, suggesting an ancient zoonotic coronavirus. Coronaviruses have been undesirable companions of populations long before the ongoing coronavirus disease 2019 outbreak emerged.